Analisis Pelayanan Obat-Obatan Dalam Kepuasan Konsumen Pada Apotek Syalom Amurang - Silalahi, Irene Sinta; Tampi, Johny R. E.; Punuindoong, Aneke Y. (Sam Ratulangi University, 2019)
This study aims to determine customer satisfaction with drug services at the Syalom Amurang Pharmacy. The focus of the research is, product quality, service quality, Emotional, Cost, and Price. The theory used in this study is the theory of Consumer Satisfaction by Lupyoadi. In this study using qualitative methods, data collection techniques are carried out through observation, interviews and documentation. The informants in this study were the Amurang City Community who had bought medicine at the Syalom Pharmacy. Location research at Syalom Amurang Pharmacy, with the basis used in law No. 25 of 2009 concerning the standard of public service, the standard of service that has been determined by the service unit, working to serve every citizen and resident to fulfill their rights is not the need for basic needs within the framework of service. Pharmacy units the importance of the service of medicines in community satisfaction can be measured by a predetermined standard, namely, service satisfaction for the services of the Syalom Pharmacy in Amurang in terms of service requirements, product quality, price, service quality, emotional, cost. From the 5 service standards there are results that state that they are not satisfied with the quality of service, product quality emotionally satisfied to eat a short service time, customer fees or rates according to and satisfied with service, price and cost, product quality, Syalom pharmacy Amurang field observation.